TESTING LIQUID LAUNDRY WASTE WELDING COMPOUND AS AN ADDITIONAL MATERIAL FOR MAKING ISENCTICIDE AGAINST BLACK ANTS MORTALITY: TESTING LIQUID LAUNDRY WASTE WELDING COMPOUND AS AN ADDITIONAL MATERIAL FOR MAKING ISENCTICIDE AGAINST BLACK ANTS MORTALITY - Humaerah, St Aisyah; Sri Magfirah HS; Nururrahmah (Cokroaminoto Journal of Chemical Science, 2024)
The use of detergent from laundry businesses which is thrown directly into water bodies causes pollution of the aquatic environment because of its large accumulation and the nature of the compound content which is difficult to break down by decomposing microorganisms in water bodies. This research aims to determine the most optimal mixing ratio for the mortality time of the test insects. This research uses a laboratory pre-experiment method with research variables between liquid laundry waste containing LAS compounds and citronella compounds from lemongrass extract, namely 2:1; 4:1 ; 6:1 ; and 8:1. This research used test insects in the form of black ants that disturb orchid plants with 3 repetitions of insecticide testing. In this study, the results of the analysis of laundry waste LAS levels were 8 mg/L with a citronella concentration of 37.62%. The test results showed that the most optimal mixing ratio for black ant test insect mortality was 2:1 with a black ant mortality time of 28 seconds.